Examining Heterogeneity in the Impacts of Socio-Emotional Curricula in Preschool: A Quantile Treatment Effect Approach - Shea, Zhiling Meng; Jenkins, Jade Marcus (Frontiers in Psychology, 2021)
We examine treatment effect heterogeneity using data from the Head Start CARES study, in which a sample of preschool centers was randomly assigned to either one of three curricula interventions targeting social-emotional (SE) skills (i.e., emotional knowledge, problem-solving skills, and executive functions) or to continue using their “business-as-usual” curriculum. Most existing research estimates only mean differences between treatment and control groups, and uses simple subgroup analyses to assess treatment heterogeneity, which may overlook important variation in treatment effects across the ex-post outcome distribution. We use quantile treatment effects analyses to understand the impacts of these curricular interventions at various parts of the outcome distribution, from the 1st percentile to the 99th percentile, to understand who benefits most from SE curricula interventions. Results show positive impacts of the curricula interventions on emotional knowledge and problem-solving skills, but not equally across the full skill distribution. Children in the upper half of the emotional knowledge distribution and at the higher end of the problem-solving skills distribution gain more from the curricula. As in the study’s original mean-comparison analyses, we find no impacts on children’s executive function skills at any point in the skills distribution. Our findings add to the growing literature on the differential effects of curricula interventions for preschool programs operating at scale. Importantly, it provides the first evidence for the effects of SE curricula interventions on SE outcomes across children’s outcome skill levels. We discuss implications for early education programs for children with different school readiness skills.